Penambatan Molekul Senyawa Turunan Beta Asaron Sebagai Antimalaria: Molecular Docking of Derivated Compounds of Asaron Beta as an Antimalaria - Salahuddin Salahuddin (Proceeding of Mulawarman Pharmaceuticals Conferences, 2021)
Beta Asarone derivatives are known for their potential as antimalarial. In the current study, the quantitave structure-activity relationship (QSAR) and molecular docking on 31 asarone derivatives was performed to search for novel more potent asarone derivatives as antimalaria. The obtained QSAR model was log IC 50 = 2.57917 + 0.019377 (AM1_HF) + 5.82755 (glob) + 0.61384 (log s) + (-1.63312 (mr)) + 0.05564 (vol). Designing new compound of asarone derivatives was performed using the validated QSAR model and the result showed that two compounds, A5 and A18, had better activities than the parent compound (ASN27). Molecular docking study showed that the two compounds were able to interact with crucial amino acid residues in the allosteric site of protein receptor (PDB code: 1CET) through hydrogen bonds and van der Waals interactions. The current study indicated that the two compounds had affinity significantly different to native ligand and might be useful to be advanced in the drug discovery process.